Działalność bydgoskiego Zarządu Wojewódzkiego PTTK w latach 1975-1990 (Kronika Bydgoska, 2014)
In 1975-1990, the Regional Board of PTTK (Polish Tourist and Sightseeing Society) in Bydgoszcz, in accordance with the Statute that was in force at that time, served as a link between the central office of the Society and branches, concentrating their activity in the territory that was specified by the Statute. It also represented these branches before regional authorities and constituted a body coordinating and supervising them in the scope of the Statute and program in the region. Political, social and economic changes in a period between the late 1980s and the early 1990s forced also essential transitions and modemization of activity of the Society, particularly in relation to implementation of the Law on Associations, in the economic aspect. The new Statute of PTTK, adopted on the 12th National Convention of PTTK on June 16, 1990, did not consider functioning of regional boards. The article presented organizational and program activity of the Board, organizational structures of the Society in the region; characterized tourist facilities in the region, cooperation with the local authorities, activity with school youth and academic, craft and military circles, as well as in the field of guiding and foreign tourism.